Does Tocilizumab Influence the Outcome of Patients with COVID-19 Pneumonia Compared to the Standard Therapy? Retrospective Analysis of Data Obtained during Phase I COVID Pandemic - Mohamed, M. Elsayed; Farouk, Khalid; Mohamed, G. Alansary; Ahmed, Abdelaziz; Mohamed, A. Shawky; Sameh, S. Taha; Amr, Hosny; Motaz, M. Elhallag (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: No gold standard therapy was approved globally for COVID-19 pneumonia to the date of this study. The pathophysiology of SARS-CoV-2 infection displayed the predominance of hyperinflammation and immune dysregulation in inducing multiorgan damage. Therefore, the potential benefits of both immune modulation and suppression in COVID-19 have been extensively discussed as a modality to control cytokine release syndrome (CRS). Abnormally high levels of interleukin-6 (IL-6) are a common finding in COVID-19 patients with pneumonia and acute respiratory distress syndrome, so the use of IL-6 antagonist was tested as a therapeutic option in controlling the disease. Tocilizumab is a recombinant humanized anti-human IL-6 receptor monoclonal antibody that can specifically bind the membrane-bound IL-6 receptor and soluble IL-6 receptor, thereby inhibiting signal transduction. Tocilizumab is currently FDA approved for the management of rheumatoid arthritis, giant cell arthritis, polyarticular juvenile idiopathic arthritis, and systemic juvenile idiopathic arthritis. This study is a retrospective analysis of data polled during Phase I of COVID pandemic, adopted by the isolation hospital of Kasr Al-Ainy Medical School, Cairo University, during the period from May to September 2020. AIM: The aim of this study is to evaluate tocilizumab influence in the outcome; in terms of reducing the hospital stay, risk and duration of mechanical ventilation (invasive and noninvasive), mortality, and the incidence of complications related to drugs use (secondary bacterial infection and GIT bleeding) in patients with moderate-to-severe COVID-19. METHODS: This retrospective, observational cohort study included adults (between 18 and 80 years) with moderate-to-severe COVID-19 pneumonia, who were admitted to isolation hospital of Kasr Al-Ainy Medical School, Cairo University, between May and September 2020. We segregated the patients into two groups: Group A: In addition to the standard care protocol according to the local guidelines of the Egyptian Ministry of Health and Population in that period (supplemental oxygen, steroids in a dose of 1–2 mg/kg methylprednisolone for 5–10 days, broad-spectrum antibiotics, vitamins, and prophylactic dose of anticoagulation with low-molecular-weight heparin, proton-pump inhibitor, and poly-vitamins), they received tocilizumab intravenously in a dose of 8 mg/kg bodyweight (up to a maximum of 800 mg per dose), divided in two shots 12–24 h apart. Group B: Those received the standard care protocol alone, noting that guidelines were adjusted later on according to the updated scientific publications and WHO recommendations. The primary endpoint was to evaluate the effect of different regimens in controlling the disease, the need for mechanical ventilation and its duration (either invasive or non-invasive), length of ICU stay, hospital stay, and in-hospital mortality. Comparisons between quantitative variables were done using the non-parametric Mann–Whitney U-test. For comparison of serial measurements within each patient, the non-parametric Wilcoxon signed-rank test was used. For comparing categorical data, Chi-square (2) test was performed. Exact test was used instead when the expected frequency was <5. Correlations between quantitative variables were done using Spearman correlation coefficient. RESULTS: During this period, 166 patients were admitted to ICU, suffering from severe hypoxemia with moderate to severe COVID-19 pneumonia, 10 of them were excluded (three were over 80 years old, other three had advanced stages of malignancy, two were on steroids therapy and non-invasive home ventilation due to chronic chest condition, and two were presented with MODs and deceased in <48 h from admission), thus, 156 were included in the study. Group A: Seventy-six patients (49%) received tocilizumab in addition to standard therapy, Group B: Eighty patients (51%) received standard therapy only. In Group A, the mean length of ICU stay was 8.96 days with mean length of hospital stay 13.76, compared to mean length of ICU stay 9 days in Group B (p = 0.57) and mean length of hospital stay 12.46 days (p = 0.117). In Group A, 35 patients (46%) needed non-invasive mechanical ventilation (MV),12 patients of the 35 needed invasive MV in later stage, compared to 26 patients (32%) in Group B, 14 patients of the 26 needed invasive MV in later stage (p = 0.16). In Group A, 14 patients (18.4%) needed invasive mechanical ventilation, compared to 19 patients (23.7%) in Group B (p = 0.213). In Group A, 6 (7.9%) of 76 patients died, compared to 13 (16.3%) of 80 in Group B p = 0.11. The incidence of secondary bacterial infection in Group A was 16 patients (21%) compared to 21 (26%) in Group B (p = 0.44). CONCLUSION: In this study, we did not detect statistical difference in both groups of patients coming during CRS-associated COVID-19 pneumonia, regarding (ICU stay, need for and length of MV, the incidence of secondary bacterial infection, and in-hospital mortality) for COVID-19 moderate-to-severe pneumonia.